2021
DOI: 10.1093/plphys/kiab166
|View full text |Cite
|
Sign up to set email alerts
|

The mobile SAR signal N-hydroxypipecolic acid induces NPR1-dependent transcriptional reprogramming and immune priming

Abstract: N-Hydroxypipecolic acid (NHP) accumulates in the plant foliage in response to a localized microbial attack and induces systemic acquired resistance (SAR) in distant leaf tissue. Previous studies indicated that pathogen inoculation of Arabidopsis (Arabidopsis thaliana) systemically activates SAR-related transcriptional reprogramming and a primed immune status in strict dependence of FLAVIN-DEPENDENT MONOOXYGENASE 1 (FMO1), which mediates the endogenous biosynthesis of NHP. Here, we show that elevations of NHP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
118
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(138 citation statements)
references
References 81 publications
16
118
1
Order By: Relevance
“…Likewise, FLA is one of the few candidates downregulated in response to fungus, UV, and drought treatments. FLA encodes a fasciclin-like arabinogalactan protein associated with both structural and signaling function in plant cell walls and, in accordance with our results, was also strongly downregulated during SAR establishment and defense priming [ 57 , 60 ], as well as in response to different distinct multi-stresses conditions [ 55 ]. All these transcriptional alterations in genes involved in cell wall dynamics suggest that biotic and abiotic stresses can trigger wall structure and integrity modifications, which may be determinants in A. stenosperma adaptation to marginal habitats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, FLA is one of the few candidates downregulated in response to fungus, UV, and drought treatments. FLA encodes a fasciclin-like arabinogalactan protein associated with both structural and signaling function in plant cell walls and, in accordance with our results, was also strongly downregulated during SAR establishment and defense priming [ 57 , 60 ], as well as in response to different distinct multi-stresses conditions [ 55 ]. All these transcriptional alterations in genes involved in cell wall dynamics suggest that biotic and abiotic stresses can trigger wall structure and integrity modifications, which may be determinants in A. stenosperma adaptation to marginal habitats.…”
Section: Discussionsupporting
confidence: 86%
“…More detailed expression analysis was conducted by qRT-PCR for another 18 A. stenosperma previously associated with priming phase ( Table S2 ), such as genes involved in secondary metabolism (IRL, STS, UGT, BBE, N8DT, and PAL); cell wall structure and integrity (EXLB, EGC, FLA, LAC, and PRP); basal defense pathways (eGCL, NUDT, SYP); or stress signal transduction (LOB, AKT) [ 8 , 19 , 55 , 56 , 57 , 58 , 59 , 60 ]. These candidate genes were selected among the 1460 metaDEGs identified here as commonly regulated by a broad range of primary stresses ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Yildiz et al (2021) confirmed that the mobile SAR signal induced by treating Arabidopsis thaliana plants with N-hydroxypipecolic acid (NHP) stimulated NPR1 mediated transcriptional reprogramming of Flavin-dependent Monooxygenase 1 (FMO1) and other downstream genes, thus systematically activating an immune response against pathogenic attack. The role of plant natural product NHP in activating immune response has been identified more recently (Yildiz et al, 2021), which is synthesized directly from pipecolic acid catalyzed by FMO1 in a series of transamination/reduction steps mediated by SARD-4 and AGD2-like defense response protein (ALD1). SA-mediated activation of NPR1 has also been shown to stimulate the ubiquitination of several cytoplasmic proteins by forming SA-induced condensates (SINC).…”
Section: Sa and No: Interplay Between Biotic And Abiotic Stress Tolerance Biotic Stressmentioning
confidence: 71%
“…It has been observed that NPR1 and SA largely control the function of HDAC19 to impose priming in plants [ 63 ]. In Arabidopsis , after pathogenic ingression, the accumulation of N-hydroxypipecolic acid (NHP) was observed, which served defence priming by inducing SAR in NPR1-dependent manner [ 64 ]. Other HDACs, such as HDA6, are also involved in JA-mediated signalling in WRKY-dependent pathways.…”
Section: Epigenetic Regulation Of Plant Memorymentioning
confidence: 99%